Biological micro resonators for whispering gallery mode lasing via droplet drying techniques - Mai Hong, Hanh; Tran Anh Duc; Nguyen, Van Anh; Nguyen Minh Nguyet; Cao Dinh Son; Quang Do, Loc; Mai Thuy Quynh; Pham Van Thanh (Communications in Physics, 2026)
In this study, we report the manufacturing and performance evaluation of biolasers based on the Whispering Gallery Mode (WGM) resonance effect, employing a solution composed of the natural protein bovine serum albumin (BSA) and the fluorescent dye Rhodamine B (RhB). Microsphere and microdisk resonators with well-defined shapes were fabricated by utilizing the micro-grating structures naturally on the surface of commercial compact discs (CDs) and adding a thin layer of edible oil. Experimental results demonstrate that both microsphere and micro disk cavities are capable of emitting laser light with clear emission spectra, characterized by low lasing thresholds of approximately 1 μJ/pulse and high-quality factors (Q-factors) reaching up to 2883, when an optical pulsed Nd:YAG laser at a wavelength of 532 nm is used to excite the cavities. The considerable flexibility and elasticity of the BSA substrate enable tuning of the emitted wavelength by adjusting the shape of the resonance cavity. These findings highlight the potential of using biocompatible, low-cost, and readily available natural materials in the development of integrated micro-optical devices for biomedical applications.